Sosialisasi Cuci Tangan Pakai Sabun Dan Pengenalan Beberapa Aplikasi Pelajaran IPA Dalam Kehidupan sehari-hari - Hadi Imam Sutaji; Ali Warsito; Bernandus Bernandus (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2024)
This community service activity aims to provide information to the students of Kupang City Leadership Madrasah Ibtidaiyah (MI) on how to the correct way of hand washing with soap (CTPS) and introduction to several applications of learning IPA in everyday life. The activities methods used are the preparation stage, implementation stage and evaluation stage. The evaluation results of activities showed that students generally of hand washing with soap (CTPS) are correctly during demonstrations and practice. Likewise the introduction to several applications of learning IPA in everyday life, students generally able to recognize and well recall the phenomena, physical quantities and some examples that have been presented when asked to mention and explain them again. These results provide confidence that carrying out this activity is an experience that can help students to always behave in a clean and healthy lifestyle wherever they are and have an interest in learning IPA.